From the family to the Biofamily - Jiménez Carbajal, Alicia Ruth (2019)
The term Biofamily can be considered a necessary neologism for studies and research about the family. This, with its customs and behaviors also acquires interest from ethics. From the ethics applied to the family the term biofamily arises, which refers to the first life group, where the person becomes human. Globalization has allowed the entry of ideologies that take the natural family from its rightful place; public policies must consider the structure and functioning of the biofamily as the foundation for the development of society. The relativization of the family concept by supranational organizations has contributed to increased confusion. The development of the concept of biofamily, in academic and research environments will allow not to distort the concept of family.